Meningkatkan Aktivitas, Keterampilan Berpikir Kritis, Dan Hasil Belajar Menggunakan Model Pigura Pada Siswa Kelas IV - Ahmad Shabirin; Akhmad Riandy Agusta (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The problem in this study is that students have not been able to develop critical thinking skills, students are still passive in learning activities, students have not been able to interact with their classmates and the learning conditions are not pleasant. This is because students are not used to thinking critically in learning activities, learning tends to use the lecture method, learning does not do group work and does not use various learning models. The effort to overcome these problems is to use the PIGURA model in learning. The purpose of this research is to describe teacher activities and to analyze the increase in activity, critical thinking skills and student learning outcomes. This research uses a qualitative approach with the type of Classroom Action Research (CAR). The research subjects were fourth grade students at SDN Kelayan Selatan 3. This research was conducted in 4 meetings, each meeting consisting of planning, implementing, observing and reflecting. The results showed that teacher activity at meeting 1 obtained a score of 42 and increased at meeting 4 to obtain a score of 60. Student activity at meeting 1 obtained a percentage of 27% and increased at meeting 4 obtained a percentage of 91%. Critical thinking skills at meeting 1 obtained a percentage of 27% and increased at meeting 4 obtained a percentage of 91%. For classical completeness student learning outcomes at meeting 1 obtained a percentage of 36% and increased at meeting 4 obtained a percentage of 91%. Based on the results of this study it can be concluded that the use of the PIGURA model can increase activity, critical thinking skills and student learning outcomes.